Recent Advances in LPSO-Containing Wrought Magnesium Alloys: Relationships Between Processing, Microstructure, and Mechanical Properties - Liu, Huan; Huang, He; Wang, Ce; Sun, Jiapeng; Bai, Jing; Xue, Feng; Ma, Aibin; Chen, Xiao-Bo (JOM (1989), 2019)
Development of strong and ductile lightweight magnesium (Mg) alloys has been the subject of enormous research breakthroughs since 2000. This review describes the most significant progress on the design and processing of high-strength wrought Mg alloys containing long-period stacking order (LPSO) phases. It first focuses on the typical atomic structure, transformation, and morphology of various LPSO phases, then explores the key contributions of thermomechanical processing techniques to the metallurgical structure, morphology, spatial dimension, and distribution of diverse LPSO phases and discusses the LPSO-derived strengthening mechanisms of Mg alloys. Finally, future research opportunities for LPSO-containing wrought Mg alloys are proposed on the basis of the mechanistic relationships between the evolution of LPSO phase particles and strengthening mechanisms.